Plurilinguisme et altérité dans les écritures - Christine Ramat (Carnets)
The scriptural practices of Sony Labou Tansi, Kossi Efoui, Koffi Kwahulé on the side of French-speaking Black Africa, or Frankétienne, Raphaël Confiant, Édouard Glissant, Patrick Chamoiseau on the side of the West Indian writings, develop a strong linguistic heterogeneousness as well as a clashing polyphony which, pushed to the excess, border on the monstrous. This verbal hybridity takes support on the sociolinguistic context of diglossia specific to Africa, but exceeds it because the writers of the “migritude” intend to assume an esthetic positioning in connection with the reality of cross-cultural Africa. Beyond, they share the same fascination for the strangeness of the literary language and think of the literary invention as the fabrication of a language which carnavalises the world and shows its chaos. These forms of multilingualism give birth to what we could call “monstrous languages”; at the same time enormous languages exhibit eccentricities. What are the main lines of this “monstrous use” of language? How does it operate? To produce which effects and defend which po-ethical values?